Highly efficient deep-blue electrofluorescence with optimized excited state composition and "hot-exciton" channel. (February 2023) - Sun, Mizhen; Li, Tengyue; Xie, Mingliang; Zhou, Huayi; Sun, Qikun; Liu, Danfeng; Pan, Yuyu; Zhang, Shitong; Yang, Wenjun; Xue, Shanfeng
Abstract: The properties of excited states of emitters play an important role in OLEDs. How to obtain balanced hybrid localized charge transfer (HLCT) state by reasonably designing molecules is still a challenge. Herein, three HLCT states D-π-A type blue fluorophores with different LE/CT hybrid degree were designed and synthesized, namely 3, 6-di-tert-butyl-9-(4-(6-(4-(4, 5-diphenyl-4 H -1, 2, 4-triazol-3-yl)phenyl)pyren-1-yl)phenyl)-9 H carbazole (DTPCZPYTZ), 3, 6-di-tert-butyl-9-(4-(4-(4-(4, 5-diphenyl-4 H -1, 2, 4-triazol-3-yl)phenyl)naphthalen-1-yl)phenyl)-9 H -carbazole (DTPCZNATZ) and 3, 6-di-tert-butyl-9-(4''-(4, 5-diphenyl-4 H -1, 2, 4-triazol-3-yl)-[1, 1':4′, 1″-terphenyl]-4-yl)-9 H -carbazole (DTPCZPHTZ). DTPCZPHTZ achieved quasi-equivalent hybrid local and charge-transfer (HLCT) excited state and efficient "hot-exciton" channel, the non-doped deep-blue device based on DTPCZPHTZ has an electroluminescence emission peak ( λ EL ) of 427 nm with Commission International de L'Eclairage (CIE) of (0.157, 0.037), the maximum external quantum efficiency (EQE) is up to 5.7% and the efficiency roll-off is only 5% (under 1000 cd m −2 ), which is outstanding in the reported deep-blue emitters. This study proved that the quasi-equivalent hybrid HLCT state is beneficial to improving device performance. Graphical abstract: This work provides a flexible and convenient method for fine-tuning the excited states of emitters, by changing the number of benzene rings in the intermediate π bridge, the degree of LE/CT hybridization can be adjusted. Finally, quasi-equivalent hybrid deep-blue luminescent emitter and highly efficient non-doped deep-blue OLED is obtained. Image 1 Highlights: Construction of quasi-equivalent hybrid local and charge-transfer (HLCT) excited state and hot exciton channels. Efficient non-doped deep-blue OLED with EQE up to 5.7% and CIE (0.157, 0.037). Highly Suppressed efficiency roll-off of only 1%–5% at 1000 cd m −2 .